Neuroprotective Effects of Virgin Coconut Oil Supplemented Diet against Sodium Benzoate-induced Acetylcholinesterase Dysfunction and Cognitive Impairment: Role of Nrf2/NfKb Signaling Pathway (Nigerian Journal of Physiological Sciences, 2022)
The effect of virgin coconut oil (VCO) supplemented diet on sodium benzoate (SB) – induced neurotoxicity in male Wistar rats was investigated. Twenty (20) male Wistar rats weighing 160-180g were divided into four (4) groups: Control which received 1ml of normal saline, SB-treated; received 200 mg/kg b.w, SB + Low Dose VCO-treated (SB + 5% VCO mixed with 95g of rat chow), and SB + High Dose VCO-treated (SB+ 15% VCO mixed with 85g of rat chow). The brain was processed for NRF-2, NF-kB, and acetylcholine esterase (AchE) gene expression levels. Also, the blood sample was processed for assessment of superoxide dismutase (SOD), catalase (CAT), and IL1B levels. One-way ANOVA and Tukey post hoc tests were used to analyze data. SB-treated rats with no intervention showed anxiety-like behavior and impaired memory as depicted by a significant (p